Transatlantic Context for Gaelic Language Revitalisation - Dunmore, Stuart S. (Studia Celtica Posnaniensia, 2020)
The notion of the ‘new speaker’, and its salience particularly in relation to minority language sociolinguistics, has become increasingly prevalent in the last decade. The term refers to individuals who have acquired an additional language to high levels of oracy and make frequent use of it in the course of their lives. Language advocates in both Scotland and Nova Scotia emphasise the crucial role of new speakers in maintaining Gaelic on both sides of the Atlantic. As a result, Gaelic language teaching has been prioritised by policymakers as a mechanism for revitalising the language in both polities. This article examines reflexes of this policy in each country, contrasting the ongoing fragility of Gaelic communities with new speaker discourses around heritage, identity, and language learning motivations. Crucially, I argue that challenging sociodemographic circumstances in Gaelic communities in Scotland and Nova Scotia contrast with current policy discourses, and with new speaker motivations for acquiring higher levels of Gaelic oracy in North America.